2022
DOI: 10.1108/jima-01-2020-0004
|View full text |Cite
|
Sign up to set email alerts
|

Does religious knowledge level affect brand association and purchase intention of luxury cars? Case of the Lexus cars in Indonesia

Abstract: Purpose This study aims to analyze the role of religious knowledge level in influencing customers’ brand association and purchase intention of luxury cars by focusing on the Indonesian context and taking the Lexus brand as a case in point. Design/methodology/approach A sample of 159 respondents was taken from a population of Muslim consumers who live in Java province, Indonesia, and who have not had Lexus luxury car but have had other cars before. Using a quantitative research approach on primary data collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 47 publications
4
28
0
Order By: Relevance
“…Fourth, the association of BA with PQ (H4) is supported and is consistent with Pinar et al (2020), Sankaran and Chakraborty (2023). Fifth, results of (H5), "association of BA with BI," concurs with Huang et al (2011), Ratnasari et al (2023, Touni et al (2022) and Bian and Liu (2011). Sixth (H6): association of PQ with BI, is consistent with Das (2014), Wang et al (2020a), Wasaya et al (2021), Srivastava et al (2022), Treiblmaier and Garaus (2023) and Garaus (2023.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Fourth, the association of BA with PQ (H4) is supported and is consistent with Pinar et al (2020), Sankaran and Chakraborty (2023). Fifth, results of (H5), "association of BA with BI," concurs with Huang et al (2011), Ratnasari et al (2023, Touni et al (2022) and Bian and Liu (2011). Sixth (H6): association of PQ with BI, is consistent with Das (2014), Wang et al (2020a), Wasaya et al (2021), Srivastava et al (2022), Treiblmaier and Garaus (2023) and Garaus (2023.…”
Section: Discussionmentioning
confidence: 66%
“…, 2020). Strong BAs are linked to high PQ, which influences purchasing decisions (Ratnasari et al. , 2023).…”
Section: Theoretical Foundation Literature and Hypothesesmentioning
confidence: 99%
“…In addition, demographic factors such as gender and education have also been found to influence a Muslim's understanding and perception of paying zakat. (Ratnasari et al, 2022) Based on the review of the research results that have been described above, it can be concluded that there are still differences from the various research results. Furthermore, the studies that explain the knowledge of zakat using quantitative approach remains scant.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the provision of halal food can potentially boost the economy [2], especially if we consider the number of adherents of Islam in Indonesia and globally. World Population Review data reported that the Muslim population in Indonesia in 2021 was 229 million out of 276 million total population, which means they account for 87.2% [3] [4], while the world's Muslim population is approximately 1.9 billion out of the 7.5 billion total world population. The halal industry contributes to Indonesia's Gross Domestic Product of US$ 3.8 billion annually [5].…”
Section: Introductionmentioning
confidence: 99%